Efeitos de um programa de treinamento com kettlebell na força muscular respiratória de mulheres jovens saudáveis - Moreira, Camila (2022)
Introduction: Kettlebell training (TKB) is considered a high intensity training, able of increasing respiratory muscle strength (FMR) of sedentary young women. Objective: To evaluate the effects of kettlebell training on respiratory muscle strength and describe the acute cardiorespiratory responses of a kettlebell training session. Methodology: The research had 18 volunteers and 12 weeks of duration in 4 phases: familiarization (2 weeks), phase I (2 weeks), phase II (4 weeks) and phase III (4 weeks). To determine respiratory muscle strength, inspiratory and expiratory pressures were evaluated using an analogic manovacuometer, according to the guidelines of the Brazilian Society of Pulmonology and Tisiology. Anthropometric measurements of weight, height and body composition were also applied. Maximum oxygen consumption (VO2max) was evaluated by a cardiopulmonary test on the treadmill, by an adapted ramp protocol. Statistical analysis: A two-way Anova was used, followed by the Sidak test, in addition to Ancova, utilized to correct the age. The maximum tolerable error was 5%. Hedges G has been corrected by the J value to calculate the effect size. Results: There was an increase in the mean of the maximal repetition test and a significant difference in expiratory muscle strength between the trained group and the control group. The size of the effect at the end of the training showed a decrease in fat percentage (14.5%), increase in VO2max (5.4%), maximum velocity (12%), 1RM (maximum repetition) (27.9%) and PEmáx (maximum expiratory pressure) (10.3%) for the trained group. Conclusion: TKB caused clinically important increases in the FMR in healthy young women.